The Subaru FMOS galaxy redshift survey (FastSound). IV. New constraint on gravity theory from redshift space distortions at z ∼ 1.4 - Okumura, T; Hikage, C; Totani, T; Tonegawa, M; Okada, H; Glazebrook, K; Blake, C; Ferreira, P; More, S; Taruya, A; Tsujikawa, S; Akiyama, M; et al. (Oxford University Press, 2016)
We measure the redshift-space correlation function from a spectroscopic sample of 2783 emission line galaxies from the FastSound survey. The survey, which uses the Subaru Telescope and covers the redshift ranges of $1.19<$z$<1.55$, is the first cosmological study at such high redshifts. We detect clear anisotropy due to redshift-space distortions (RSD) both in the correlation function as a function of separations parallel and perpendicular to the line of sight and its quadrupole moment. RSD has been extensively used to test general relativity on cosmological scales at $z<1$. Adopting a LCDM cosmology with the fixed expansion history and no velocity dispersion $σ_{\rm v}=0$, and using the RSD measurements on scales above 8Mpc/h, we obtain the first constraint on the growth rate at the redshift, $f(z)σ_8(z)=0.482± 0.116$ at $z\sim 1.4$ after marginalizing over the galaxy bias parameter $b(z)σ_8(z)$. This corresponds to $4.2σ$ detection of RSD. Our constraint is consistent with the prediction of general relativity $fσ_8\sim 0.392$ within the $1-σ$ confidence level. When we allow $σ_{\rm v}$ to vary and marginalize it over, the growth rate constraint becomes $fσ_8=0.494^{+0.126}_{-0.120}$. We also demonstrate that by combining with the low-z constraints on $fσ_8$, high-z galaxy surveys like the FastSound can be useful to distinguish modified gravity models without relying on CMB anisotropy experiments.